Simulando - do mundo maravilhoso das distribuiç\~oes contrafatuais - Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– This discussion paper presents a methodology to visualize the effects of various influences on the income distribution. The methodology, although not new, has become very popular in the past few years. It is the method of counterfactual simulations. In other words, it is the use of "what if …" questions in the study of income distribution. The method is applied to Brazil to visualize the effects of type of employment status, region, economic activity sector, and educational endowment on the income distribution of 1998.
Keywords: 330; Einkommensverteilung; Theorie; Brasilien